Probabilistic presentation of the geometric properties of shipbuilding structural profiles when assessing elastic bending strength - 362016 Ivanov, Lyuben D. (Houston, TX : American Bureau of Shipping, 2001)
V.1 Theory -- v.2 Numerical examples.